Near Trench 3D Seismic Attenuation Offshore Northern Hikurangi Subduction Margin, North Island, New Zealand. Issue 3 (17th March 2021) - Nakai, Jenny S.; Sheehan, Anne F.; Abercrombie, Rachel E.; Eberhart‐Phillips, Donna
Abstract: We image seismic attenuation near the Hikurangi trench offshore New Zealand, using ocean bottom and land‐based seismometers, revealing high attenuation above a recurring shallow slow‐slip event and within the subducting Hikurangi Plateau. The Hikurangi subduction margin east of the North Island, New Zealand is the site of frequent shallow slow slip events. Overpressured fluids are hypothesized to lead to slow slip at shallow depths close to the oceanic trench. Seismic attenuation, energy loss of seismic waves, can be used to detect high temperatures, melt, the presence of fluids, and fractures. We use local earthquake P‐ and S‐waves from 180 earthquakes to invert for t *, and subsequently invert for Qp and Qs, offshore the North Island directly above the area of slow slip. We image Qp and Qs to ∼25 km depth, increasing resolution of previously identified coastal low Q (100–300), and finding a new region of even higher attenuation (Qp and Qs < 50–100) directly above the shallow slow slip event of 2014–2015, beneath the offshore seismic array. This highest attenuation is downdip of a subducting seamount, and is spatially correlated with a high seismic reflectivity zone and Vp/Vs > 1.85, all of which provide evidence for the presence of fluids. The Qp and Qs is low at the trench (<50–100) and in the subducting plate (100–200), suggesting that seismic wave scattering due to faults, fractures, and the inherent heterogeneous composition of the Hikurangi Plateau, a large igneous province, plays a role in seismic attenuation. Plain Language Summary: The Hikurangi Margin is a major subduction zone which has produced earthquakes that lead to tsunamis, which could endanger people living on the North Island of New Zealand and the fishing and shipping industry. Mysterious slow earthquakes, or slow slip events, happen near the shore where large earthquakes have happened in the past. Scientists do not yet understand why these events occur, but it may be because of fluids on the plate that is subducting beneath the North Island. These fluids can come from chemical reactions or the water content of the sediment on the incoming plate. Our study finds evidence of fluids in the area of the plate interface by measuring energy loss from earthquakes offshore of the North Island, which we use to create a 3D image of where energy is lost. As seismic waves travel through rock, they lose a lot of energy when they encounter fluids, like water, and as they pass through layered, volcanic rocks. We combine our study with other studies to show where pockets of fluids are likely located near the subducting plate, which will help scientists in future field studies and also help us understand why slow slip events occur at the Hikurangi Margin. Key Points: Low Qp and Qs (<50–100) coincides with high Vp/Vs and are interpreted as fluid near the plate interface, downdip of a subducted seamount Low Qp (100–200) in the Hikurangi Plateau large igneous province suggests a thicker (~23 km) oceanic crust Near‐trench low Qp and Qs (<50–100) may indicate seismic wave scattering from faults in the Hikurangi Basement and the deformed upper plate